2015
DOI: 10.1093/jae/eju033
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Economic Growth in Africa: An Econometric Analysis

Abstract: The economic landscape of most Africa countries depends essentially on the dynamics of climate change. Key sectors driving their economic performance and livelihoods such as agriculture, forestry, energy, tourism, coastal and water resources are highly vulnerable to climate change. This paper examines the empirical linkage between economic growth and climate change in Africa. Using annual data for 34 countries from 1961 to 2009, we find a negative impact of climate change on economic growth in Africa. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 25 publications
7
59
0
Order By: Relevance
“…This is because most farming income is generated from these poorer regions, which are also rather dry. This finding was consistent with previous studies, which found that rainfall had positive impacts on the economic growth of poor and arid countries that were reliant on rainfed agriculture (Abidoye and Odusola 2015;Ali 2012;Lanzafame 2014;Miguel and Satyanath 2011;Sequeira et al 2018). In addition, the Mekong River is a major source of water for both northern and northeastern regions.…”
Section: Economic Sector Resultssupporting
confidence: 93%
“…This is because most farming income is generated from these poorer regions, which are also rather dry. This finding was consistent with previous studies, which found that rainfall had positive impacts on the economic growth of poor and arid countries that were reliant on rainfed agriculture (Abidoye and Odusola 2015;Ali 2012;Lanzafame 2014;Miguel and Satyanath 2011;Sequeira et al 2018). In addition, the Mekong River is a major source of water for both northern and northeastern regions.…”
Section: Economic Sector Resultssupporting
confidence: 93%
“…Scholars have shown empirical and practical pieces of evidence for impact of climate change on GDP growth in different countries. Using a basic cross-country growth regression model, Abidoye and Odusola (2015) provided estimates of the impact of climate change on GDP growth in 34 African countries. Using a similar model, Barrios et al (2010) estimated the impact of rainfall on GDP growth in an empirical economic growth framework of sub-Saharan African nations compared with other developing nations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The foregone consumption and investment as a result of lower income during the period of higher temperature (lower precipitation) distorts the growth process. Also, heavy investment on adaptation and mitigation programmes will impose some opportunity costs, especially in terms of not investing such resources on science, technology and innovations as well as human and physical capital investment (Pindyck, 2011;Ali, 2012;andOdusola, 2012 and2015). The resources spent on climate change adaptation and mitigation have the tendency of crowding out investment on other vital drivers of growth and development, especially spending on education, health and infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%